High Performance of Human Resource Practice Towards Work Engagement: A Practice at a Government Public Office - Agung Prasetyo; Majang Palupi (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2023)
This study aims to examine and analyze the effect of high-performance human resource practice on work engagement in the Secretary Office of the Regional House of the Representatives City of Dumai by using indicators of high-performance human resource practices, which consist of extensive training, employment security, participation and communication, selection and recruitment, and reward and compensation as independent variables. This quantitative research had a total sampling technique of 100 respondents. Data was collected by distributing questionnaires which were then processed using the IBM SPSS 26 application. The results indicated that the variables of extensive training, selection and recruitment, and reward and compensation had a positive and significant impact on work engagement. At the same time, the variable employment security had a positive but insignificant impact on work engagement. The variable of participation and communication had a negative but insignificant impact on work engagement.